Where is ’the Crescent’ in ’the Meeting of the Cross and the Crescent’? The Place of Islam in Western Historiography of the Crusades, 1950-2007 - Rubenstein, Barak (Jama’a: an Interdisciplinary Journal of Middle East Studies, 2009)
For centuries, Western intellectuals regarded the Crusades to the Levant (late 11th- late 13th centuries) as a part of the history of Western Christianity. Most of the scholarly literature written in the West in modern times analyzes the Crusader-Muslim encounter, mainly or solely, from the perspective of the Crusaders. Since World War II, however, Western historiography has dedicated more attention to the Middle Eastern contexts of the Crusaders’ activities, and to developments among the Crusaders’ local Muslim rivals. This article demonstrates this change through a comparative analysis of several studies, spanning Steven Runciman’s monumental work of the 1950s to textbooks of recent years. According to the interpretation suggested here, the change in scholarly discourse is an outcome of certain political and social currents, changing intellectual trends, and the personal, professional and ideological inclinations of scholars.